The values you endorse set the body you see: The protective effect of intrinsic life goals on men's body dissatisfaction. Issue 4 (30th March 2022) - Ku, Lisbeth; Newby, Charis; Moldes, Olaya; Zaroff, Charles M.; Wu, Anise M. S.
Abstract : The mass media portrayal of a muscular body type ideal has been increasingly tied to men's body image dissatisfaction. We examined the role of self‐determination theory's intrinsic life goals within this body image ideal and its potential as a moderator of this dissatisfaction. We first tested the moderating effect of intrinsic life goals on the link between magazine consumption and body image dissatisfaction via an online questionnaire (Study 1; N  = 826), then experimentally manipulated these goals and exposure to images of muscular male models (Study 2; N  = 150). A robust protective effect of intrinsic goals on body image satisfaction was observed – the relationship between magazine consumption and body image dissatisfaction was only significant among individuals with a lower level of intrinsic life goal orientation. When participants' intrinsic goals were momentarily heightened, they reported significantly less body image dissatisfaction, compared to those not receiving a strengthening of these goals. The results are the first to find a protective effect of intrinsic life goals on men's body image, and have important implications for intervention.